Vertebroplasty and balloon kyphoplasty in osteoporosis: friends or foes? - Marcucci, Gemma (CIC Edizioni Internazionali, 2009)
Osteoporotic vertebral fractures are a common cause of pain and disability and increased mortality in western countries. We have analyzed three studies about Vertebroplasty and Balloon Kyphoplasty that have been recently published. We discuss potential complications, results of each technique, and whether the long-term outcome is similar in patients treated with Vertebroplasty and Balloon Kyphoplasty and non-surgical treatment, to decide the correct use of these minimally invasive techniques and for such patients.